Treatment of Basal Cell Carcinomas with Pulsed Dye Laser: A Case Series - Norman Minars; Marianna Blyumin-Karasik (Journal of Skin Cancer)
Background. Basal cell carcinoma (BCC) is the most prevalent skin cancer. Because of its highly vascular characteristic, it is amendable to treatment with pulse dye laser (PDL). The goal of this study is to determine the safety and efficacy of PDL therapy for mostly facial BCCs. Materials and Methods. Sixteen men and thirteen women (29 total) with 39 biopsy-proven BCCs were treated with 1–4 PDL (595 nm) therapies at 2–4-week intervals. The treatment parameters included pulse energy of 15 J/cm 2, pulse length of 3 millisecond, with no dynamic cooling, and 7 mm spot size. The age of the patients was 30–90 years (mean 73 years). Response rates were evaluated by the clinical assessments with mean followup of 11 months. Results. Twenty-four patients with thirty-two tumors reached at least three months followup: 24/32 (75%) tumors with complete resolution (mean 3 treatment sessions); 5/32 (16%) tumors recurred; 3/32 (9%) tumors with incomplete responses after four treatments. Minimal side effects and discomfort were experienced by the patients with PDL therapy. Conclusion. PDL is a safe, tolerable, and moderately effective method of treating various BCCs. The ideal niche and standardized settings for PDL treatment of BCCs are yet to be determined.